MODELS FOR IMPROVING THE PSYCHOLOGICAL TRAINING OF MILITARY PERSONNEL - Melikuziev , R.Sh; Murodov , M.M (Innovative Development in Educational Activities, 2023)
This article deals with the problem of psychological training of military personnel; the urgency of this problem is emphasized, since the current level of development of the Armed Forces of the states makes high demands on the professional training of military personnel. The author presents the positions of scientists who reveal the concept of psychological preparation, and also gives his own definition of this phenomenon. The article also contains a description of the types and forms of general, special and targeted psychological training aimed at creating the necessary resources for military personnel to perform tasks for their intended purpose.